High-Power Diode Laser Technology and Applications XIII 2015
DOI: 10.1117/12.2077617
|View full text |Cite
|
Sign up to set email alerts
|

Development of high-power diode lasers with beam parameter product below 2 mm×mrad within the BRIDLE project

Abstract: High power broad-area diode lasers are the most efficient source of optical energy, but cannot directly address many applications due to their high lateral beam parameter product BPP = 0.25 × Θ L 95% × W 95% (Θ L 95% and W 95% are emission angle and aperture at 95% power content), with BPP > 3 mm×mrad for W 95%~9 0µm. We review here progress within the BRIDLE project, that is developing diode lasers with BPP < 2 mm×mrad for use in direct metal cutting systems, where the highest efficiencies and powers are requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…However, an alternative explanation presents itself. In recent work, resonant anti-guiding structures have been shown to reduce BPP 0 without other negative effects, attributed to a reduction in the number of lateral modes supported for a given thermal profile [8]. However, even when the number of modes is reduced to 1, BPP 0 does not reduce to the diffraction limit [8].…”
Section: Analysis and Interpretationmentioning
confidence: 92%
See 1 more Smart Citation
“…However, an alternative explanation presents itself. In recent work, resonant anti-guiding structures have been shown to reduce BPP 0 without other negative effects, attributed to a reduction in the number of lateral modes supported for a given thermal profile [8]. However, even when the number of modes is reduced to 1, BPP 0 does not reduce to the diffraction limit [8].…”
Section: Analysis and Interpretationmentioning
confidence: 92%
“…In recent work, resonant anti-guiding structures have been shown to reduce BPP 0 without other negative effects, attributed to a reduction in the number of lateral modes supported for a given thermal profile [8]. However, even when the number of modes is reduced to 1, BPP 0 does not reduce to the diffraction limit [8]. Therefore, we propose instead that the offset in BPP 0 from the diffraction limit is a measure of both number of guided modes and of non-ideality in the system, such as a complex form of the thermal lens or material non-uniformity.…”
Section: Analysis and Interpretationmentioning
confidence: 98%
“…A low vertical divergence is beneficial to the use in a CBC setup, where tolerances in the alignment of the collimation lenses impact the achievable combining efficiency 14 . Furthermore, previous studies have shown that this amplifier design can also deliver high beam quality in slow axis with an improved power content in the central lobe 15,16 . A drawback is, however, its reduced electrical to optical efficiency 16 .…”
Section: Amplifier Design For High-efficiency Cbcmentioning
confidence: 96%
“…Furthermore, previous studies have shown that this amplifier design can also deliver high beam quality in slow axis with an improved power content in the central lobe 15,16 . A drawback is, however, its reduced electrical to optical efficiency 16 . We used 5 mm long devices (1 mm ridge + 4 mm taper) mounted p-side up on CuW heat spreaders and C-mounts, with separate electrical contacts in order to control the injection current of ridge (Irw) and tapered section (Itp) independently.…”
Section: Amplifier Design For High-efficiency Cbcmentioning
confidence: 96%
“…Важный научный и технологический вклад в разработку систем спектрального суммирования был внесён в ходе выполнения исследований по Европейскому проекту BRIDLE (bright diode laser), в котором приняли участие практически все ведущие европейские промышленные компании и университеты [42]. Были созданы монолитные ЛЛД, каждый кластер которых имеет разную длину волны излучения с заданным периодом по ширине излучающей апертуры и представляет собой тандем в виде одномодового задающего генератора и усилителя (MOPA -Master oscillator -Power amplifier).…”
Section: современные достижения в области формирования требуемых параunclassified